Interference and Compatibility Analysis of RF Communication Systems (MEASAT -Case Study) - Leghari, Zulfiqar Ali; Othman, Abdul Rani; Muhammed, Ghulam (2006)
The paper will demonstrate a case study of detailed Interference and Compatibility Analysis of MEASAT networks vis-a-vis affected satellite networks having the orbital separation less than 8°. For detailed interference and compatibly analysis of Measat-SA3 (370 E) and Paksat-2 (410 E) for C band uplink and downlink we have carried out analysis under ITU-R REC-740 [1]. The analysis demonstrates that two collocated satellite networks at the orbital separation of less than 5 degree can be operated in Cband for digital and analog communications without generating and accepting harmful interference [5]. For smooth and interference free transmission, both of the satellite networks have to be limited in radiating the power in up and down links. The analysis proposes power limits and constraints for both of the satellite systems for smooth and interference communications in both directions.